Predictive Performance of Serum β-hCG MoM Levels for Preeclampsia Screening: A Meta-Analysis - Zhang, Xiao; Huangfu, Zhao; Shi, Fangxin; Xiao, Zhen (Frontiers in Endocrinology, 2021)
Objective: The aim of the present study was to investigate the predictive value of using the multiple of the median (MoM) of β-human chorionic gonadotropin (β-hCG) levels in patients with preeclampsia (PE) and healthy pregnant women. Methods: Electronic databases including PubMed, EBSCO, Ovid, Web of Science, China National Knowledge Infrastructure (CNKI), SinoMed, Wangfang and the Weipu Journal were searched up to May 31, 2020. Two reviewers independently selected the articles and extracted data on study characteristics, quality and results. A random-effects model was employed, and standardized mean difference and 95% confidence intervals were calculated. Twenty-one case-control studies were analyzed in the present meta-analysis, including a total of 2,266 cases and 25,872 healthy controls. Results: Women who were diagnosed with PE were found to have higher early second-trimester levels of serum β-hCG MoM compared with healthy controls, although the levels in the first trimester were not significantly different. Ethnicity subgroup analysis demonstrated that the MoM of β-hCG serum levels was significantly higher in PE patients in both Asian and Caucasian populations during the early second trimester. Conclusion: The MoM of β-hCG serum levels was found to be a valuable clinical indicator for predicting PE in the early second trimester, but had little predictive value in the first trimester. However, further assessment of the predictive capacity of β-hCG within larger, diverse populations is required.